NEP 2020: Bridging India’s Skill Gap in Higher Education - Kumari Rajpriya (IJRDO- Journal of Educational Research, 2025)
The National Education Policy (NEP) 2020 is meant to be a major change that will change India’s education system, notably for higher education. One of its most important contributions is that it tries to close the long-standing gap between the skills needed in academics and those needed in the business world. India still has trouble finding jobs for its graduates, even if the number of graduates is going up every year. This is because of old curriculum, a lack of ties to the industry, a lack of vocational integration, and a lack of digital literacy. NEP 2020 tackles these problems by pushing for education that crosses disciplines, flexible curricula, the inclusion of vocational training, a focus on new and digital technologies, and the creation of ecosystems for research and innovation. This paper critically analyzes NEP 2020 within the framework of India’s higher education talent gap, evaluates the existing literature and traditional research approaches employed to investigate analogous changes, and underscores the implementation issues. The report indicates that NEP 2020 provides a revolutionary framework; however, successful implementation, ongoing evaluation, and robust collaboration between industry and academics are crucial to equip India’s youth with the necessary skills for the 21st-century global economy.